Organization Structure Municipally, Ready To The Organizational Incorporation Of The Information Technologies - Galván, Israel Patiño; Pizano, J. Jesús Ceja (Advances in Social Sciences Research Journal, 2017)
The Information Technologies (IT) Have empowered and optimized human activities in various disciplines, including the local public administration, and this has resulted in process transparency, optimization of resources, collaboration in decision making, projections, optimization, among other advantages. However, it is necessary to have a technological infrastructure that guarantees the incorporation and permanence of these technologies in the long term, and more important, to have a specialized organizational structure that oversees planning, developing, implementing, projecting and collaborating in the evaluation Constantly of the processes, as well as of the technologies, that have an innovative impact in the operative and administrative processes of the municipal administration. However, in the municipal public administrations, these advantages have not been integrated, much less think about their permanence, for this, this article suggests a specialized organizational structure that can guarantee the use of IT in the long term. This proposal is supported by inductive and deductive methodologies, field research that was carried out in a sample of Mexican municipalities and their current organizational structures that are responsible for managing and operating IT.